Measuring poverty in Britain as a multi-dimensional concept, 1991 to 2003 - Tomlinson, M; Walker, R; Williams, G (2008)
While poverty is widely accepted to be an inherently multi-dimensional concept, it has proved very difficult to develop measures that both capture this multi-dimensionality and facilitate comparison of trends over time. Structural equation modelling appears to offer a solution to this conundrum and is used to exploit the British Household Panel Study to create a multi-dimensional measure of poverty. The analysis reveals that the decline in poverty in Britain between 1991 and 2003 was driven by falls in material deprivation, but more especially by reduced financial stress, particularly during the early 1990s. The limitations and potential of the new approach are critically discussed. © 2008 Cambridge University Press.